Enhanced photosensitization of zinc oxide nanorods using polyaniline for efficient photocatalytic and photoelectrochemical water splitting. (14th December 2016) - Sharma, Surbhi; Singh, Simrjit; Khare, Neeraj
Abstract: Polyaniline (PANI) coupled Zinc oxide (ZnO) nanocomposite has been synthesized by the chemisorption method and demonstrated its potential applications for photocatalytic degradation of methylene blue dye and photoelectrochemical (PEC) water splitting. A ∼7 fold enhancement in the photodegradation activity and ∼3 fold enhancement in the incident photon-to-electron conversion efficiency is observed for PANI/ZnO nanocomposite as compared to bare ZnO nanorods. The observed enhancement in the photocatalytic and photoelectrochemical activity is attributed to the photosensitization effect of visible light responsive PANI and the formation of type-II heterojunction between ZnO and PANI leading to the efficient separation and faster transfer of photoinduced charge carriers at the interface. A possible mechanism for the enhanced photocatalytic activity and photoelectrochemical water splitting for PANI/ZnO nanocomposite has been proposed. Graphical abstract: PANI/ZnO nanocomposite has been synthesized by coupling visible light active polyaniline (PANI) with ZnO nanorods via simple chemisorption method. The PANI/ZnO nanomposite exhibited remarkable improvement in photocatalytic efficiency and IPCE for PANI/ZnO composite as compared to ZnO. The enhancement in photocatalytic and photoelectrochemical activity of ZnO after loading of PANI is attributed to the higher separation efficiency of photogenerated charge carriers due to the formation of type-II heterojunction between PANI and ZnO. Highlights: PANI/ZnO composite has been synthesized by chemisorption method. PANI/ZnO exhibit ∼7 fold enhancement and ∼3 fold enhancement in photocatalytic and photoelectrochemical activity. The photosensitization role of PANI has been demonstrated for the enhancement in photocatalytic and photoelectrochemical activity.